Teach For America and Teach For All: Creating an Intermediary Organization Network for Global Education Reform - La Londe, Priya Goel; Brewer, T Jameson; Lubienski, Christopher A (Education Policy Analysis Archives, 2015)
Locally and globally among policymakers and edupreneurs, what constitutes “good teaching and learning” is highly contested, and prototypes that seem to embody “what works” are highly valued. In the United States, many accept Teach For America (TFA) as an exemplar of “what works.” As its U.S. operations continue to grow, TFA has recalibrated and expanded into Teach for All, an international organization with extensive reach. Teach For All not only finds historic roots in TFA, but it reflects TFA’s intentional expansion of its theory of change and implementation on a global scale. This exploratory essay investigates the linkages between TFA and TFAll, focusing on theory and implementation of education reform by comparing domestic TFA ideology and practices with those of TFAll. Also, we conceptualize the dimensions and anatomy of a global network of IOs engaged in global education reform. In addition to providing insight on TFAll, our broader goal is to build the knowledge base around what we are calling global Intermediary Organization Networks (IONs).